Pengaruh Variasi Kecepatan Putar Dan Jarak Penekanan Terhadap Kekuatan Impak Pada Sambungan Baja AISI 4140 Dan AISI 4340 Dengan Metode Pengelasan Gesek (Friction Welding) - Syaifullah R, L. M.; Rodika, Rodika; Ary Wahyudie, Ilham (Jurnal Inovasi Teknologi Terapan, 2023)
Welding is one of the means to achieve better economic production and has a role in the construction and metal fields. Friction welding is one of several types of welding methods. The parameters that affect the strength of the joints in friction welding are rotational speed, pressing distance and friction time. Therefore, to produce connection strength in a production, appropriate parameters are needed. This study aims to determine the effect of variations in rotational speed and pressing distance on impact strength in AISI 4140 and AISI 4340 steel joints. mm. In this study, the results obtained were that the higher the rpm rotation and the greater the pressure distance given, the melting area in the welding joint area is wide and evenly distributed which makes the weld joint strong. This is proven, using a rotational speed of 1400 rpm and a pressing distance of 4 mm has the highest impact energy yield value of 138.349 Joules and the highest impact price yield value of 1.7293 Joules/mm2 . Meanwhile, the lowest value of the impact energy yield is 14.266 Joules and the lowest value of the impact price is 0.1783 Joules/mm2 using a rotational speed of 720 rpm and a pressing distance of 2 mm.